Students’ creative activity organization in the training course at pedagogical university - Білоус, Олена Сергіївна (Educational Dimension, 2017)
The organization of students’ creative activity during their education at high school is scientifically substantiated in the article. The purpose of the article is to show that the positive dynamics of the organization of students’ creative activity in the training course at pedagogical university is associated with the identification of the need for personal and professional growth, a non-standard implementation of learning tasks, a strong interest of students to selfdevelopment, self-improvement and professional self-affirmation. A theoretical analysis and highlight of the main characteristics of creativity are done in the article. The result of the analysis presents the motives of actions that encourage the person to creative activities for the need to exercise themselves, namely: the need to exercise themselves; desire to be recognized; creative interest; passion for the creative process; desire to achieve the highest productivity in the specific conditions of their work. Nowadays, one of the ways to achieve the goal in the educational process of higher education -the organization of students’ creative activities at high school, as future teachers is interactive teaching methods, namely: heuristic conversation, presentations, discussions, «brainstorming», business game, practical work with further discussion, role play, training, creative tasks’ team decision, case method, practical exercises, group and individual exercises, simulation of manufacturing processes or situations that reflect the essence of the teacher’s future profession. A system of creative tasks to ensure the implementation of students’ creative activity at high school is developed. The question of determining ways of improving the quality of students’ training at high school and ensuring a high level of professionalism is the prospect of further research.